(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1864)
The author begins by speculating on the languages that may have influenced the development of Old Scots. He argues that it is more useful to analyse the development of the language by focusing on the grammatical features of the language rather than individual words. The article compares the grammar in Barbour’s Bruce and the Wyntoun Chronicle to the grammar used in Chaucer and other English texts. In his concluding marks, the author emphasises that this is only preliminary research that he hopes will encourage others to study Old Scots.